Entrepreneurial Skills and Performance of Pharmaceutical Firms in Anambra State Nigeria - Daniel Chukwuma Ejike; Michael Ikenna Anyika; Henry Sonna Ojukwu (Pinisi Journal of Entrepreneurship Review, 2024)
This study is an eye-opener for pharmaceutical students to learn from the experience of older pharmaceutical retail businesses on survival skills required in Nigeria's health sector. The study examined how registered pharmaceutical retail enterprises in Nigeria's Anambra State performed with their entrepreneurial qualities. The research used a descriptive survey methodology. Using Taro Yamane’s statistical technique from 1961, a sample of 180 community pharmacy practitioners in the Nigerian state of Anambra with 328 registered licenses was selected. Regression and correlation analyses were the utilized statistical methods. The study results show that entrepreneurial mentoring and innovative capability significantly favours the success of pharmaceutical retail firms in the Nigerian state of Anambra. The study concludes that developing entrepreneurial abilities is essential for improved performance, regardless of how skilled community pharmacy practitioners may be. There were some recommendations in keeping with the study's findings.